Pentingnya Taharah dalam Praktik Amalan Ibadah: Kajian Terhadap Sholat, Mandi Wajib dan Wudhu di SDN 8 Bokat. - Ni’mah Wahyuni; Ratih A. Haming; Erliana Monggu; Rianti Beddu; Ariansyah As Makur (CV. KAMPUS AKADEMIK PUBLISING, 2024)
the community that is carried out must be better understood by students, especially classes V and VI, where those who do not know or lack knowledge about what is applied and conveyed must be in accordance with the propositions of the Al-Qur'an and Hadith regarding taharah (ablution, obligatory bathing, and prayer) so that can be implemented well and able to practice it perfectly : In community service carried out at SDN 8 Bokat, Bokat District, Kodolagon Village. This activity includes material about taharah, namely ablution, obligatory bathing and prayer. The target of this community service activity is carried out on students in classes V and VI. The method used in community service is exposure and training on taharah material (ablution, obligatory bathing and prayer) which will be presented to students. The initial step in collecting data was a survey of the place where community service activities were carried out which included a briefing on the material to be presented. By presenting material and asking questions to students at SDN 8 Bokat, the results of the service process